A Hybrid Framework for Software Clone Detection - Neha Saini, Sukhdip Singh, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Software systems are becoming increasingly complex, and managing them is a critical topic in the software business today. Cloning is one of the fundamental factors that makes software maintenance more difficult. Code cloning is a copy-paste approach for reproducing code portions. Developers find it simple to copy and paste code throughout the early stages of a project's development. This paper presents a hybrid framework for detecting code clones. To detect code clones, it combines a token-based technique with metrics-based technique. Initially, metric based technique is applied to locate prospective clones. After identifying prospective clones, token-based comparison is done to confirm that they are indeed clones.